Profil Peresepan Obat Antituberkulosis Pasien Rawat Jalan Di Rumah Sakit “X” Kota Surabaya: Periode Januari-Juni 2021 - Vidya Kartikaningrum; Diah Nurcahyani; Andita Nur Wijayanti; Hervina Kusuma Dewi (Lembaga Pengembangan Kinerja Dosen, 2022)
Tuberculosis (TB) is an infectious disease caused by infection with the bacteria Mycobacterium tuberculosis that attacks the lungs or other organs of the body. The availability of antituberculosis drugs is an important thing related to the success or failure of treatment. The purpose of this study was to determine the profile of antituberculosis drug prescribing in outpatients with a diagnosis of tuberculosis at Hospital X Surabaya for the period January - June 2021. This study used an observational research type using descriptive analysis, data collection was carried out retrospectively, namely by taking secondary data through prescription sheets for patients diagnosed with tuberculosis containing antituberculosis at Hospital X Surabaya using a random sampling technique from a total of 770 prescriptions. Based on the research results, it can be seen that the most widely prescribed antituberculosis drugs are the generic drug rifampin 600 mg (17%) and the patent drug pehadoxin forte (26%). The use of combination antituberculosis was 90,63% and single therapy was 9,37%.